Assessing physical symptoms during the postpartum period: reliability and validity of the primary health questionnaire somatic symptom subscale (PHQ-15) - Stephanie Wilkie; Ros Crawley; Susan Button; Alexandra Thornton; Susan Ayers (Taylor & Francis Group, 2018)
Introduction: This study aimed at establishing the reliability and validity of the primary health questionnaire (PHQ-15) somatic symptom severity subscale for postpartum women. Methods: Women (N = 495) completed the PHQ-15 approximately 6 weeks postpartum during the baseline phase of a randomized controlled trial evaluating a writing intervention for postnatal health in England. Reliability was assessed using internal consistency statistics and convergent validity by comparing differences in self-reported physical health, health-related quality of life (QoL) and primary care usage by PHQ-15 symptom severity category. Results: Cronbach's α for the PHQ-15 was 0.73 and item-total statistics met recommended guidelines. Validity analyzes showed 6% of women reported severe symptoms, 17% medium, 50% low and 27% minimal symptoms. Women with severe symptoms reported poorer overall physical health, poorer physical health-related QoL and greater use of primary care. Women with severe symptoms also rated their baby's health as worse and used primary care more for their baby. Discussion: This study suggests the PHQ-15 has the potential to be a useful and valid measure of physical symptoms in postpartum women in high-income countries.